Occult bacteremia in living donor liver transplantation: a prospective observational study of recipients and donors - Yao, Siyuan; Yagi, Shintaro; Sugimoto, Takuya; Asahara, Takashi; Uemoto, Shinji; Hatano, Etsuro (Surgery Today, 2024)
Purpose To investigate the incidence and clinical impact of occult bacteremia in liver transplantation (LT). Methods This prospective observational study involved a fixed-point observation for up to 2 weeks after living donor LT in 20 recipients, with 20 donors as comparison subjects. Bacteria in the blood samples were detected using the ribosomal RNA-targeted reverse-transcription quantitative polymerase chain reaction method. To identify the causality with the gut microbiota (GM), fecal samples were collected and analyzed simultaneously. Results Occult bacteremia was identified in four recipients (20%) and three donors (15%) before the operation, and in seven recipients (35%) and five donors (25%) after the operation. Clostridium leptum subgroup, Prevotella , Colinesella , Enterobacteriaceae, and Streptococcus were the main pathogens responsible. Although it did not negatively affect the donor post-hepatectomy outcomes, the recipients with occult bacteremia had a higher rate of infectious complications post-LT. The GM analyses showed fewer post-LT predominant obligate anaerobes in both the recipients and donors with occult bacteremia. Conclusions Occult bacteremia is a common condition that occurs in both donors and recipients. While occult bacteremia generally remains subclinical in the healthy population, there is potential risk of the development of an apparent post-LT infection in recipients who are highly immunosuppressed.